2014
DOI: 10.1002/ccd.25328
|View full text |Cite
|
Sign up to set email alerts
|

Balloon aortic valvuloplasty in high risk aortic stenosis patients with left ventricular ejection fractions <20%

Abstract: Objectives: To determine outcomes following balloon aortic valvuloplasty (BAV) in aortic stenosis (AS) patients with a left ventricular ejection fraction (LVEF) <20%. Background: Severe AS patients with a LVEF <20% are excluded from United States (U.S.) transcatheter aortic valve replacement (TAVR) trials and often surgical aortic valve replacement (AVR). The role for BAV to enhance LVEF is unclear. Methods: Our BAV database of 270 consecutive patients extending from 2005 through 2010 was queried for a preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
4
4
0
Order By: Relevance
“…Also, in consistent with the observed studies, the ventricular dysfunction improved significantly in all the age groups after BAV 15 . Pedersen et al have demonstrated the same even in the elderly population 16, 17. All the patients in the present study underwent BAV using low-profile Tyshak II balloon, which have shown good results in various studies 18 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, in consistent with the observed studies, the ventricular dysfunction improved significantly in all the age groups after BAV 15 . Pedersen et al have demonstrated the same even in the elderly population 16, 17. All the patients in the present study underwent BAV using low-profile Tyshak II balloon, which have shown good results in various studies 18 .…”
Section: Discussionsupporting
confidence: 89%
“…Our restenosis rate was comparable and aortic insufficiency rate and surgical rate were lower than many other reported studies 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. O Reich et al 4 followed up over a period of 15 years showed restenosis rate of 16.7% ( n = 45) and significant insufficiency in 22.3% ( n = 60); surgery was needed in 20.1% ( n = 54), and “valvuloplasty failure” occurred in 41.6% ( n = 112) of patients.…”
Section: Discussionsupporting
confidence: 67%
“…Most studies report a small change in valve area following BAV, and this was true in our series. Although the change was statistically significant, the difference was not enough to explain the marked improvement in symptoms we observed.…”
Section: Discussionsupporting
confidence: 82%
“…We found that nearly half of patients with baseline LV dysfunction experienced early improvement in LVEF after TAVR, while less than one-third of patients do so with standard therapy. This improvement in LV systolic function during standard therapy is largely attributable to optimisation of medical management as well as to balloon aortic valvuloplasty (BAV) 19 20. Patients with LV systolic dysfunction and severe AS are exquisitely sensitive to afterload,21 and previous studies have shown that the modest reductions in LV pressure load seen with BAV can lead to improved LV function 22 23…”
Section: Discussionmentioning
confidence: 99%